(3CjeGf GdYQH aj GdLGgdjIs - (3GdfLjQej , EHQGgje Hf YHO Gddg Hf eMeO GdfLjQej, CHh ESMGb,J (B355 (3g` s
(3ChdgG (B:s
(3cGfJ GdYQH ai GdLGgdjI ai ePGgH TJi s
(3BNQgG (B:s
(3BdjJ MH GdYQGb CWYeg GdHjJ gPG BNQ cJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B49 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B55s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B202 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B40 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI TgjO Ydi (B(2394(2)) s
Keywords: (3GdJGQjNs